ANALYSIS OF CURRENT STATE AND PERSPECTIVES OF MODERNIZATION OF MACHINE OF THE SLUGS NO 3 CONTINUOUS CASTING AT RUP «BMZ» - V. A. Matochkin; V. E. Marushkevich; O. P. Krasjuk (Литьë и металлургия)
The current state is analyzed and perspectives of modernization of machine of the slugs continuous casting at Belorussian metallurgical works are given.